INFEKSI TOXOPLASMOSIS, RUBELLA, CYTOMEGALOVIRUS DAN HERPES SIMPLEX VIRUS (TORCH) SEBAGAI FAKTOR RISIKO NEURAL HEARING LOSS (NHL) PADA ANAK - , Tumpal Simatupang; , Dr. Kartono Sudarman, Sp.THT-KL (K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Congenital hearing loss is still a health problem in children that can cause delays in speech and language development. One type of hearing loss in children is Neural Hearing Loss (NHL). The number of events pretty much, but the diagnosis of NHL in children is often overlooked. Congenital TORCH infections was suspected to increase the risk of NHL. Purpose: To determine the TORCH infections can increase the risk of NHL. Methods: A case-control study conducted in Dr. Sardjito General Hospital based medical records since January 2010 until March 2014. All children aged less than 18 years who has done BERA examination at the Electromedic Division Dr. Sardjito General Hospital and TORCH examination is the subject of this research. TORCH infection was defined by one or more of the results of serological Toxoplasma, Rubella, CMV and HSV tested positive. Results: There were 76 children who were included in this study. TORCH infection is an independent risk factor for NHL (aOR 18.73, 95% CI 5.65 to 62.01,p0.01). Conclusion: TORCH increase the risk of NHL in children.